The process of opening innovation networks: open innovation at Embrapa Florestas (INMR - Innovation & Management Review, 2022)
Purpose – The purpose of this paper is to map the process of opening an innovation network in the context of the Brazilian agroforestry sector.Design/methodology/approach – Qualitative case study of the open innovation network Embrapa Florestas (17 semi-structured interviews, observation and documentary data). Social network analysis (SNA) of the open innovation network from primary data is available at Embrapa Florestas’ system.Findings – Three primary triggers to the opening process of Embrapa Florestas’ innovation network were identified. The process starts with an innovation network with closed network characteristics. The process of opening the innovation network is motivated by a restructuring in its source of fundraising (trigger 1), by the change in strategic orientation toward the internationalization of its network activities (trigger 2) and by opening the black box of its innovation with greater proximity to the productive sector and partner universities (trigger 3). Comparing the pre-opening and post-opening networks (open innovation network), sociometric data allows us to verify that the opening of the innovation network presents better density, clustering and centrality indexes for the network as a whole and for the Embrapa Florestas specifically.Originality/value – This is one of the first studies that aims to investigate the transition from a closed innovation network to an open innovation network by a public research institute. It may also be considered innovative because it presents practical and managerial relevance – in addition to contributions to public policy makers – which allows for improvements in the development of innovation and technology in the country’s strategic sectors.